Analysis of LMNB1 Duplications in Autosomal Dominant Leukodystrophy Provides Insights into Duplication Mechanisms and Allele‐Specific Expression. Issue 8 (28th May 2013) - Giorgio, Elisa; Rolyan, Harshvardhan; Kropp, Laura; Chakka, Anish Baswanth; Yatsenko, Svetlana; Gregorio, Eleonora Di; Lacerenza, Daniela; Vaula, Giovanna; Talarico, Flavia; Mandich, Paola; Toro, Camilo; Pierre, Eleonore Eymard; et al.
<x xml:space="preserve">Abstract</x> Autosomal dominant leukodystrophy (ADLD) is a demyelinating disorder caused by duplications of the LMNB1 gene. Detailed molecular analysis of the largest collection of ADLD families studied, to date, has allowed us to identify the minimal duplicated region necessary for the disease, identify the first inverted LMNB1 duplication and characterize genomic features and mutational mechanisms that may play a role in duplication formation. Analysis of allele specific LMNB1 expression reveals similar expression levels for both copies of the duplicated gene. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>